2022
DOI: 10.1186/s12891-022-05888-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of femoral mechanics before and after internal fixation removal and the effect of sclerosis on femoral stress: a finite element analysis

Abstract: Background Femoral neck fractures are a common traumatic injury. The removal of the internal fixation remains controversial, especially in terms of mechanical stability. Moreover, collapsed necrosis of the femoral head continues to occur after fracture healing. We believe that sclerotic cancellous bone (SCB) formation around the screw is associated with femoral head necrosis. We aimed to compare mechanical features before and after implant removal and determine the effect of SCB formation on st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…The most serious complication of femoral neck fracture is avascular necrosis of the femoral head and internal xation failure [21,22], and there are many factors leading to these complication, such as the age of the patient, general health status, combined underlying diseases, injury mechanism, fracture displacement, osteoporosis, etc., and the above factors cannot be controlled by the doctor [23,24]. What can interfere is the operation time, the quality of fracture reduction and the choice of internal xation.…”
Section: Complicationsmentioning
confidence: 99%
“…The most serious complication of femoral neck fracture is avascular necrosis of the femoral head and internal xation failure [21,22], and there are many factors leading to these complication, such as the age of the patient, general health status, combined underlying diseases, injury mechanism, fracture displacement, osteoporosis, etc., and the above factors cannot be controlled by the doctor [23,24]. What can interfere is the operation time, the quality of fracture reduction and the choice of internal xation.…”
Section: Complicationsmentioning
confidence: 99%
“…A prior finite element analysis by our team indicated that the presence of sclerosis poses a risk of femoral head collapse, even in cases of proper FNF healing 8 . The bone trabeculae surrounding the screw paths experience strains ranging from 1000 to 3000 με, which leaves these sites in a responsive osteogenic phase, leading to sclerotic bone formation.…”
Section: Introductionmentioning
confidence: 97%